The Analysis of the Standardization of the Sizing of Muslim Women’s Clothing in Indonesia - E Nurbaity A; Suryawati .; E Lutfia Zahra (KnE Social Sciences, 2019)
This study aims to analyze the standard size of Muslim women’s clothing used by the ready-to-wear industry. This research includes aspects of the type of Muslim clothing, the standard system of sizes used, variations in the size and the level of customer satisfaction with Muslim clothing. The research method uses the mixed method that combines qualitative and quantitative research. The study was conducted in Jakarta by taking samples from the three largest shopping centers in Indonesia, with a total of 70 respondents with accidental sampling techniques. The results of the analysis show that Muslim women’s clothing products in some markets use garment sizes. The clothing size is influenced by the form of clothing (design), price, and the type of material. Some Indonesian designers refer to body measurements with modifications according to the design. Muslim fashion women with robe forms dominate the market, especially in Jakarta. The robe or syar’i clothing generally uses the size of the body circumference and the length of the dress as a reference in determining the standard size. The difference in the size based on shapes is obtained 1–2 cm between standards, based on the price, the difference in size reaches 2–4 cm, and differences based on materials between 1–2 cm. The level of satisfaction with Muslim women’s clothing based on design/form, consumers stated that they were very satisfied, while for the level of satisfaction with standard sizes, variations in size and price, consumers expressed satisfaction and normality on the packaging aspect.  Keywords: standard size, body size, garment, size in label